The Role of Educational Management in Developing Teachers' Digital Competencies as the Key to Successful Technology-Based Learning - Meti Wigiyantini; Asep Rahmat Kurnia; Rohayanah; Winda Widiastuti; Nuryaningsih Pulungan; Maman Suryaman (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The rapid advancement of digital technology has reshaped the educational landscape, yet many elementary school teachers still struggle to integrate technology effectively into instruction. This research addresses the gap between managerial support and teachers’ digital competence in achieving successful technology-based education. Guided by educational management theory and the digital competence framework, this study analyzes how the role of educational management and teachers’ digital skills affect learning success. Using a quantitative explanatory survey involving 105 elementary school teachers in Karawang Regency, data were collected through a five-point Likert-scale questionnaire and analyzed using SPSS. The results show that both variables significantly influence technology-based learning success (p = 0.000, R² = 0.684). These findings highlight that visionary and adaptive school management, combined with strong teacher digital competence, are key drivers of educational transformation. The study contributes theoretically to the discourse on digital pedagogy and, practically, to strengthening managerial strategies in digital-era schooling. Keywords: educational management, teachers' digital competencies, technology-based learning, educational transformation